2013
DOI: 10.3109/09638288.2013.872200
|View full text |Cite
|
Sign up to set email alerts
|

Exploring staff experience of an “enriched environment” within stroke rehabilitation: a qualitative sub-study

Abstract: Results from animals models suggest that environmental enrichment (EE) is an important paradigm for consideration in stroke rehabilitation. It is concerning that many stroke survivors are inactive during their admission for inpatient stroke rehabilitation. Preliminary results suggest that rehabilitation nurses perceive that EE promoted patient activity/participation. Results highlight the importance of social support and participation in the ward environment and potential benefits for patient's mood levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…13 As shown in Table 2 and also confirmed by others, 15 patients with the most severe strokes spent most time in bed, indicating that, the need for help in mobilization probably represents a barrier to initiate transfer to the communal areas. 22 …”
Section: Motor Activitymentioning
confidence: 97%
“…13 As shown in Table 2 and also confirmed by others, 15 patients with the most severe strokes spent most time in bed, indicating that, the need for help in mobilization probably represents a barrier to initiate transfer to the communal areas. 22 …”
Section: Motor Activitymentioning
confidence: 97%
“…Studies have demonstrated an interdependency between the physical environment, patient care and rehabilitation after stroke that may affect a patients’ recovery after stroke, in some cases hindering the recovery process [20, 21]. Thus, it is of utmost importance to increase our understanding of whether and how the physical environment can support an individual’s ability to adapt to and interact with his or her immediate surroundings after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…We do not know whether this resulted from the locations of the lounge and therapy area, which made it impossible to invite patients to visit those rooms, or whether it was a result of the room design, which was not sufficiently stimulating or attractive. Studies have shown that patients are more likely to be engaged in activities in enriched environments than in non‐enriched environments (Janssen et al., ; White et al., ). Modern stroke units need to consider the evidence for enriched environments and design lounges and therapy areas that support activities and social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Research based on animal models (Johansson & Belichenko, ) has suggested that an enriched environment can promote recovery after a stroke. In addition, studies in real stroke care have shown that an enriched environment can promote both cognitive and social activities (Janssen et al., ; White, Bartley, Janssen, Jordan, & Spratt, ; White et al., ). The specific features of an enriched environment are access to meeting places, for example, patient lounges and the potential for individual activities, for example, access to computers, books, newspapers, games and personal hobbies (Janssen et al., ; Keysor, Jette, Coster, Bettger, & Haley, ).…”
Section: Introductionmentioning
confidence: 99%